A Daily Activity Monitoring System for Internet of Things-Assisted Living in Home Area Networks - Hyun-Sik Kim; Jong-Su Seo; Jeongwook Seo (Institute of Advanced Engineering and Science, 2016)
In this paper, a daily activity monitoring system for Internet of Things (IoT)- assisted living in home area networks is proposed in order to provide care for elderly people who live alone. The proposed system consists of two main parts: an IoT-assisted living space with contactless activity sensors, a help trigger, and an emergency gateway and a daily activity monitoring server with a range of components including data collection, event and user management, activity analysis and reporting, and so on. The contactless activity sensors can be placed anywhere in the home, and the emergency gateway collects data from them, detects emergency situations reported through the help trigger, and communicates with the daily activity monitoring server. The server analyzes and reports the daily activities and activity patterns of elderly users using a predefined activity index. In addition, unexpected emergency situations can be estimated and prevented through analysis of the activity information.